Interrogation and torture integrating efficacy with law and morality - Gaggioli, Gloria; Fallon, Mark; Barela, Steven J. 1971- (New York, NY Oxford University Press, 2020)
This book focuses on the science, law and morality behind interrogational methods. It develops, for the first time, a comprehensive discussion regarding the legality of torture and the efficacy of interrogation. In other words, scientific research has concluded that torture is not effective. This then raises a natural question: What interrogational methods are effective? How does one employ those methods in way that is consistent with law and morality?"--
Introduction : Legal, Moral and Effective Interrogation / Steven J. Barela. Jens David Ohlin -- Defining Torture and the Obligation of Systematic Review in the CAT Treaty / Manfred Nowak, Giuliana Monina -- Personality Disruption as Mental Torture : The CIA, Interrogational Abuse, and the U.S. Torture Act / David Luban, Katherine S. Newell -- The Field of Torture Today : Ten Years On from Torture and Democracy / Darius Rejali -- The HIG Project : The Road to Scientific Research on Interrogation / Mark Fallon, Susan E. Brandon -- Developing Rapport and Trust in the Interrogative Context : An Empirically-Supported Alternative / Laure Brimbal, Steven M. Kleinman, Simon Oleszkiewicz, Christian A. Meissner -- Investigative Interviewing : From England to Norway and Beyond / Ray Bull, -- Asbjørn Rachlew -- Interrogating the Brain : Torture and the Neuroscience of Humane Interrogation / Shane O'Mara -- Professional Standards in the Aftermath of Torture : The Struggles of the American Psychological Association / Stephen Soldz, Steven Reisner -- What Can Be Asked of Interrogators? / Michael Skerker -- Beyond Ethics on the Sly : The Behavioral Sciences and National-Security Interrogation / M. Gregg Bloche -- Cycles of Compulsion : Efficacy and Legality in the History of Israeli Torture Debates and Practice / Karin Loevy -- A Qualified Defense of the Obama Administration's Record on Torture / John T. Parry -- Unmasking the Challenges : Interrogation and International Law / Gloria Gaggioli, Pavle Kilibarda -- Torture, Dignity and the Rule of Law / J.M. Bernstein -- Justifying Too Much : Utilitarianism as a Moral Theory / Bob Brecher -- Reclaiming Bentham on Torture / Steven J. Barela -- Preventing Torture : What Works? / Mark Thomson, Barbara Bernath -- Repairing the Damage from Illegal Acts of State : The Costs of Failed Accountability for torture / Claire Finkelstein, Steve Xenakis -- Drinking from a Poisoned Chalice : A Portrait of the U.S. Military Commissions at Guantánamo / John G. Baker, Mary E. Spears, Katherine S. Newell -- Setting Universal Standards for Non-Coercive Interviews and Associated Safeguards / Juan E. Méndez, Andra Nicolescu -- Afterword : The Corrosive Strategic Legacy of Torture / Alberto Mora.
Includes bibliographical references and index.
Keywords: Police questioning. -- Electronic books; Military interrogation; Torture (International law); Torture -- Law and legislation -- United States